2019
DOI: 10.1159/000504372
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Induced Cardiac Abnormalities in Rats: Attenuation via Sandalwood Oil

Abstract: <b><i>Introduction:</i></b> The clinical use of doxorubicin (DOX) is challenged by its incremental dose-related cardiotoxicity. <b><i>Objective:</i></b> The aim of the hereby study was to investigate sandalwood essential oil (SEO) against DOX-induced cardiac toxicity. <b><i>Methods:</i></b> Male Sprague-Dawley rats were allocated into 4 groups. Groups 1 signified the control, whereas group 2 administered 100 mg/kg/day SEO, both act as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The results of current study regarding oxidative stress and apoptosis pathways were in accordance with similar studies that used the same studied dose of DOX (34,35,37,39). Moreover, our findings were also in line with previous studies of different models of DOX-induced cardiotoxicity (1,6,36,(60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 92%
“…The results of current study regarding oxidative stress and apoptosis pathways were in accordance with similar studies that used the same studied dose of DOX (34,35,37,39). Moreover, our findings were also in line with previous studies of different models of DOX-induced cardiotoxicity (1,6,36,(60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of sandalwood oil at suppressing inflammation was shown by the attenuation of several pro-inflammatory mediators including IL-1β, TNF-α, and NF-κβ. 149 This study has served to corroborate prior studies performed by our lab whereby elevations in inflammatory biomarkers is a key contributor to the pathogenesis of DOX+TRZ-mediated cardiotoxicity. Specifically, our lab has shown that several markers of inflammation including NF-κβ, TNF-α, IL-1β, and IL-6 are elevated in a chronic 6-week study of DOX+TRZ-mediated cardiotoxicity in a female murine model.…”
Section: Inflammationsupporting
confidence: 80%
“…16,66,77,78,102,141 In a recent preclinical study, Younis et al (2020) investigated the cardioprotective capabilities of sandalwood oil in ameliorating DOX-induced cardiac abnormalities in rats. 149 In their rat model of DOX-induced cardiotoxicity, supplementation with sandalwood oil effectively abated the robust inflammatory response induced by DOX. The effectiveness of sandalwood oil at suppressing inflammation was shown by the attenuation of several pro-inflammatory mediators including IL-1β, TNF-α, and NF-κβ.…”
Section: Inflammationmentioning
confidence: 99%
“…In addition, a significant decrease in HR was observed in rats treated with doxorubicin (Aygün & Gul, 2019; Razmaraii et al, 2016). Moreover, DOX (3 mg/kg every 48 hr for 2 weeks, intraperitoneally) enhanced QRS duration and extended QTI and STI but decreased RRI (Younis, 2020). Co‐treatment of A‐MG and DOX could improve these alterations by increasing HR and shortening RRI, QTI, and STI.…”
Section: Discussionmentioning
confidence: 99%